1992
DOI: 10.1037/1040-3590.4.4.473
|View full text |Cite
|
Sign up to set email alerts
|

The Marital Satisfaction Questionnaire for Older Persons.

Abstract: Five studies were conducted to construct and psychometrically evaluate a marital satisfaction questionnaire for older persons. The questionnaire content was generated and refined in Study 1. Temporal stability was evaluated in Study 2, and criterion-related validity was examined in Study 3. Norms, factor structure, and construct validity of the questionnaire were established in Study 4. The degree to which scores on the questionnaire predicted observer ratings of marital interactions during an analog problem-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 46 publications
0
41
1
1
Order By: Relevance
“…The Marital Satisfaction Questionnaire for Older Persons (MSQFOP; Haynes et al, 1992) was used to measure marital satisfaction. A total score based on 17 of the 20 items in the MSQFOP was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The Marital Satisfaction Questionnaire for Older Persons (MSQFOP; Haynes et al, 1992) was used to measure marital satisfaction. A total score based on 17 of the 20 items in the MSQFOP was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Caregiver level of neuroticism was targeted based on previous carer personality research that has shown that this is the only key trait associated with caregiver adverse outcomes (Hooker et al, 1994) and this was assessed using the Eysenck Personality Questionnaire (EPQ, Eysenck and Eysenck, 1991). Caregiver relationship quality with the patient was assessed using a suitably adapted Marital Satisfaction Questionnaire For Older Persons (MSQFOP, Haynes et al, 1992) and the caregiver's experience of adverse life events was assessed using the List of Threatening Life Events Questionnaire (LTEQ, Brugha et al, 1985). There was also consideration of demographic factors such as; carer age, relationship to the patient, gender and illness duration.…”
Section: Predictor Variablesmentioning
confidence: 99%
“…These items were selected from the 20 items of the Marital Satisfaction Questionnaire for Older Persons (MSQFOP; Haynes et al, 1992) that assessed one's satisfaction with specific areas of the marital relationship. The six selected items had the highest factor loadings on the Marital Satisfaction Scale Score.…”
Section: Measurementsmentioning
confidence: 99%